The associations of early specialisation and sport volume with musculoskeletal injury in New Zealand children. Issue 2 (February 2020) - McGowan, Jody; Whatman, Chris; Walters, Simon
Abstract: Objective: To investigate associations of early specialisation (highly specialised before age 13 years) and sport participation volume with injury history in New Zealand children. Design: Cross-sectional survey study. Methods: Children attending a national sports competition were invited to complete a questionnaire capturing specialisation level (high, moderate or low), participation volume and injury history. Multiple logistic regression was used to investigate associations between variables. Results: Nine hundred and fourteen children (538 female) completed the questionnaire. After adjusting for age, sex and hours of weekly sport participation, the odds of reporting an injury history were not significantly higher for early specialised children compared to children categorised as low specialisation (OR = 0.88; CI = 0.59–1.31; p = 0.53). Participating in more hours of sport per week than age in years (OR = 2.42; CI = 1.27–4.62; p = 0.02), playing one sport for more than 8 months of the year (OR = 1.60; CI = 1.07–2.36; p = 0.02), or exceeding a 2:1 weekly ratio of organised sport to recreational free-play hours (OR = 1.52; CI = 1.08–2.15; p = 0.02), increased the odds of reporting a 'gradual onset injury'. Conclusion: Early specialisation in one sport did not increase the odds of reporting a history of injury. Exceeding currently recommended sport participation volumes was associated with increased odds of reporting a history of gradual onset injury.